How do the principals' democratic leadership styles contribute to teacher performance? - Nellitawati Nellitawati (Global Econedu, 2020)
One factor influencing teacher performance is the principal’s leadership style. For this reason, this study aims to analyze how the contribution of the principal’s democratic leadership style to teacher performance. The research method used is a quantitative non-experimental method which is correlational. The research sample is 86 elementary school teachers. Research data were collected using two instruments, the teacher’s performance questionnaire, and the democratic leadership style questionnaire. Data analysis techniques using product-moment correlation to see the significant relationship on each variable. The results showed there was a significant relationship between democratic leadership styles and teacher performance, so it can be concluded that democratic leadership styles contribute to teacher performance.